Neurotoxicity of Engineered Nanomaterials: Testing Considerations - Eleonora Scarcello; Adriana Sofranko; Tina Wahle; Roel P. F. Schins (Frontiers Media S.A., 2022)
As with toxicology in general, major challenges have emerged in its subfield neurotoxicology regarding the testing of engineered nanomaterials (ENM). This is on the one hand due to their complex physicochemical properties, like size, specific surface area, chemical composition as well as agglomeration and dissolution behavior in biological environments. On the other hand, toxicological risk assessment has faced an increasing demand for the development and implementation of non-animal alternative approaches. Regarding the investigation and interpretation of the potential adverse effects of ENM on the brain, toxicokinetic data are relatively scarce and thus hampers dose selection for in vitro neurotoxicity testing. Moreover, recent in vivo studies indicate that ENM can induce neurotoxic and behavioral effects in an indirect manner, depending on their physicochemical properties and route of exposure. Such indirect effects on the brain may proceed through the activation and spill-over of inflammatory mediators by ENM in the respiratory tract and other peripheral organs as well via ENM induced disturbance of the gut microbiome and intestinal mucus barrier. These ENM specific aspects should be incorporated into the ongoing developments of advanced in vitro neurotoxicity testing methods and strategies.